Combined Use of Modified Alvarado Score and USG in Decreasing Negative Appendicectomy Rate at Darbhanga Medical College And Hospital, Bihar, India - Surendra Kumar; Shiva Nand; V.S. Prasad (International Journal of Health and Clinical Research, 2021)
Introduction: Appendicitis is notorious in its ability to simulate other conditions and in the frequency it can be mimicked by other pathologies. Despite extraordinary advances in modern radiography imaging and diagnostic laboratory investigations the accurate diagnosis of acute appendicitis remains an engimatic challenge. Of the various commonly used diagnostic aids for appendicitis, no single test can reduce the rate of negative appendicectomy to zero. Materials and methods: Fifty admitted cases of suspected appendicitis were subjected to ultrasonography (U SG). All the patients were scored out of 9 according to modified Alvarado score. A treatment plan was devised according to which patients with modified Alvarado score  underwent immediate appendicectomy even if USG was negative for appendicitis and patients with score <7 underwent appendicectomy if USG was positive for appendicitis. Result: 84.3% of males and 44.4% of females admitted as case of suspected appendicitis has confirmed appendicitis. Due to high sensitivity (97-14% and accuracy (92%) of our diagnostic approach, 85.71% cases of appendicitis were diagnosed in early stage, with only 8.5 7% perforation and abscess rate, leading to post appendicectomy complication rate of only 5.14% in our study (one wound infection and one urinary retention). We could achieve low negative appendicectomy rate of 7.14% in males and 11.11% in females and overall 8.11% in our study. Conclusion: Combined use of modified Alvarado score and high frequency USG not only reduces negative appendicectomy rate but also reduces morbidity and postoperative complications.